PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSETS TURNOVER TERHADAP PERTUMBUHAN LABA RUMAH SAKIT YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA MASA COVID 19 - Aris Listiyono; Elfreda Aplonia Lau; Catur Kumala Dewi (Exchall: Economic Challenge, 2022)
This study aims to determine and analyze the effect of the current ratio, debt to equity ratio, total assets turnover on the profit growth of hospitals listed on the Indonesia Stock Exchange during the covid 19 period. 8 hospitals that went public and were actively used as research samples and used data financial statements in the fourth quarter of 2019, the first and third quarters of 2020. The results show that the current ratio has an insignificant negative effect on profit growth, as well as the debt to equity ratio and total assets turnover have an insignificant negative effect on profit growth. . The findings of this study also show that simultaneously the current ratio, debt to equity ratio, total assets turnover have no significant effect on the profit growth of 8 hospitals that went public during the covid 19 pandemic.